2022
DOI: 10.1177/03635465221074694
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Revision Rates of Pediatric ACL Reconstruction in New York State

Abstract: Background: There are limited epidemiologic data examining the incidence of pediatric anterior cruciate ligament reconstruction (ACLR) over the past decade. Purpose: To examine statewide population trends in the incidence of ACLR in a pediatric population. Study Design: Descriptive epidemiology study. Methods: Inpatient and outpatient claims for pediatric patients who underwent ACLR between 2009 and 2017 were identified in the New York Statewide Planning and Research Cooperative System database via Internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“… 18 , 19 Furthermore, the mean age for their study was 22 years of age and numerous studies have shown adolescents and teenagers to be the age groups with greatest incidence and risk of ACL tear and graft failure after reconstruction. 20 , 21 , 22 , 23 , 24 , 25 This increase risk could be due to hormonal changes as the ACL is now known to host sex hormone receptors. However, the mechanism is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 19 Furthermore, the mean age for their study was 22 years of age and numerous studies have shown adolescents and teenagers to be the age groups with greatest incidence and risk of ACL tear and graft failure after reconstruction. 20 , 21 , 22 , 23 , 24 , 25 This increase risk could be due to hormonal changes as the ACL is now known to host sex hormone receptors. However, the mechanism is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, Brodeur et al identified a decrease in this trend between 2014 and 2017 and suggested that injury prevention programs may be part of the reason for the improvement. 27 There is little that is known about the overall implementation and utilization of ACL IPPs among youth athletes in North America. In addition, the level of awareness of ACL IPPs parents of young athletes is unknown.…”
Section: Key Conceptsmentioning
confidence: 99%
“… 8 Overall, ACL revision rates range from 7 to 8% at 10 years postoperatively and may be slightly higher in the pediatric population. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%